Blockchain technology in maritime industry - Peronja, Ivan (Array, 2020)
Maritime industry is one of the most globally connected industries that include transportation of numerous types of goods and documents across the world. With that said, it is safe to say that abundance of financial and paper-trail transactions are made every day in order for goods to be transported from one place to another. The scope of this paper is to show that by implementing blockchain technology savings in time and money could be generated. This paper presents costs of container freights and rates in the last few years and assumes possible future costs of container freights and rates if blockchain based technology is implemented. Additionally, by using comparative method economical and time value of “traditional” bill of lading is compared with a blockchain bill of lading solution. It is also important to mention the potential impact of the blockchain technology on the world environment and ecology by reducing global paper consumption and emissions from vehicles that are used in the transportation process. This paper also gives a descriptive and comprehensive overview of current and future applications of blockchain technology in maritime industry.